PENGEMBANGAN PENDIDIKAN KARAKTER DALAM KURIKULUM MUATAN LOKAL BERBASIS BUDAYA DAERAH PADA SISWA SEKOLAH DASAR - Supeni, Siti; Farida Sari, Ama; Sutoyo, Sutoyo; Nur Oktavia, Bella (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Character education is important in the content of the elementary school curriculum. The content of this curriculum can be constructed on local content subjects, in addition to conveying material as well as strengthening character according to local customs and culture. The development of character education that contains traditional values and local culture is important because it sees the reality on the ground that school children are very dependent on gadgets but are not used for educational activities, and in making decisions for the future they are still very dependent and centered on parents' decisions. So that the service team from the Unisri PPKn study program was motivated to provide workshops on the implementation of regional culture-based local content curricula. Methods Implementation of activities is carried out in the form of counseling and training in implementing a local content curriculum based on regional culture. The results of community service activities at SDN 01 Bumi Laweyan include teachers starting to carry out and apply local culture in daily learning activities such as greetings, greeting fellow friends, and with teachers using fine Javanese. Keywords: Regional Culture, Implementation, Character Education